Digital zenith camera for vertical deflection determination - Abele, Māris; Balodis, Jānis; Janpaule, Inese; Lasmane, Ieva; Rubans, Augusts; Zariņš, Ansis (Geodesy and Cartography, 2012)
Recent accomplishments in advancement of accurate astrometric reference star catalogues, development of digital imaging technology, high accuracy tiltmeter technology, and geocentric coordinate availability provided by GNSS, have made possible accurate, fast and automated determination of vertical deflections using astrometric methods. Zenith cameras for this kind of measurements have been developed or are being developed by several research groups. The paper describes a research project by Institute of Geodesy and Geoinformation, intended to design a portable digital zenith camera for vertical deflection determination with 0.1” expected accuracy. Camera components are described, proposed data processing algorithm and preliminary results, obtained with prototype instrument, are presented.